2022
DOI: 10.3389/fimmu.2022.973600
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and associated factors among infertile couples undergoing assisted reproductive treatment

Abstract: Although periconception vaccination is important to maternal and neonatal health, little is known about the COVID-19 vaccine hesitancy among infertile couples seeking fertility treatment. Thus, we conducted this survey among infertile patients in a reproductive medicine center, between September 2021 and December 2021, to estimate the prevalence of COVID-19 vaccine hesitancy and its influencing factors. Information was collected through face-to-face interviews among volunteers. Among the 987 included interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Existing data support the idea that, after successful IVF, couples experienced more psychological problems during pregnancy [ 44 ], especially anxiety and stress, caused mainly by concern for the well-being of the unborn child. Studies conducted during the COVID-19 pandemic identified IVF as being positively associated with vaccine hesitancy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing data support the idea that, after successful IVF, couples experienced more psychological problems during pregnancy [ 44 ], especially anxiety and stress, caused mainly by concern for the well-being of the unborn child. Studies conducted during the COVID-19 pandemic identified IVF as being positively associated with vaccine hesitancy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As of January 2023, >13 billion doses of the vaccine had been administered worldwide, with an excellent safety and efficacy profile. However, as reproductive toxicity has not been evaluated in clinical trials, one reason for vaccine hesitancy is its potential negative effects on fertility [33].…”
Section: Effects Of Sars-cov-2 Vaccination On Semen Quality: Availabl...mentioning
confidence: 99%
“…Most of the studies published to date shed light on the attitude of pregnant or breastfeeding patients ( 7–10 ) and little is known about the vaccination status, attitudes and concerns among patients planning to conceive, e.g., those undergoing fertility treatment. Previous studies reported hesitant attitudes of infertile couples toward vaccination ( 12 ) but did not illuminate in detail the reasons to decide against vaccination. However, since pregnancy itself is a risk factor for a severe course of COVID-19 ( 6 ), women already intending to become pregnant should also be persuaded to be vaccinated.…”
Section: Introductionmentioning
confidence: 97%